PENGARUH KONEKTIVITAS TRANSPORTASI LAUT-DARAT DAN KONTRIBUSI EKONOMI KABUPATEN KEPULAUAN MERANTI TERHADAP KINERJA PELABUHAN TANJUNG HARAPAN - Meylan, Wellyn Cesharina; Fitri, Syakirah Athiyyah; Ridhoni, Naila Septa; Ramadhan, Melani Noviantori (SINERGI : Jurnal Riset Ilmiah, 2025)
Tanjung Harapan Port is a key transportation infrastructure in Meranti Islands Regency, Riau Province. This study aims to analyze the influence of sea-land transportation connectivity and economic contribution on the performance of Tanjung Harapan Port for operational optimization and regional economic development. A descriptive quantitative method was used by analyzing numerical data from 100 respondents in Meranti Islands Regency through purposive sampling. Data were collected using a Google Form questionnaire based on the Likert scale and analyzed using SPSS version 27 through validity, reliability, normality, multiple linear regression, T-test, and determination coefficient tests. The F-test results indicate that maritime-land transportation connectivity and economic contribution simultaneously have a significant impact on port performance with a significance level of (0.000 < 0.1). The Adjusted R-squared value of 0.649 indicates that variables X1 and X2 contribute 64.9% to port performance. Partially, sea-land transportation connectivity has a significant effect (0.001 < 0.1), while economic contribution is more dominant with significance (0.005 < 0.1). Economic contribution plays a more dominant role in improving port performance. Recommendations include improving infrastructure with e-ticket technology, developing economic zones around the port through community empowerment, and expanding research with a larger sample size.